A cross-sectional study of hypertensive outpatients to determine the necessity of asking about erectile dysfunction symptoms - N Sharifuddin; AF Abdul Aziz; MS Hamzah; R Abdul Rashid; Z Zainuddin; SEW Puteh; MZ Abdul Hamid; NA Aziz (Taylor & Francis, 2024)
Background: Erectile dysfunction (ED) is common amongst hypertensive men. Hypertensive patients often attribute it to antihypertensive drugs, although conflicting evidence linking ED with antihypertensive medication exists. The objectives were to determine the prevalence and severity of ED, the type of treatment sought, and the risk factors for ED among hypertensive men.